2009
DOI: 10.1099/vir.0.007997-0
|View full text |Cite
|
Sign up to set email alerts
|

Ovine PRNP untranslated region and promoter haplotype diversity

Abstract: The diversity and possible contribution of non-coding regions of the prion protein (PrP) gene (PRNP) to transmissible spongiform encephalopathy susceptibility and PrP regulation are not fully known. This study defined ten ovine PRNP promoters and five untranslated region (UTR) haplotypes found in atypical and classical scrapie cases and healthy control sheep. A greater diversity of promoter and UTR haplotypes was observed in conjunction with the ARQ PrP allele (seven promoter and four UTR haplotypes), while it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Whilst the majority of resistant sheep carry at least one TARQ allele, there are two Suffolk sheep and numerous Romney sheep that exhibit BSE resistance in the absence of the TARQ allele. Therefore, some other, as-yet-unknown factor, potentially a non-coding region of the PRNP gene (Saunders et al, 2009), must be responsible in these cases.…”
mentioning
confidence: 99%
“…Whilst the majority of resistant sheep carry at least one TARQ allele, there are two Suffolk sheep and numerous Romney sheep that exhibit BSE resistance in the absence of the TARQ allele. Therefore, some other, as-yet-unknown factor, potentially a non-coding region of the PRNP gene (Saunders et al, 2009), must be responsible in these cases.…”
mentioning
confidence: 99%
“…Polymorphisms within the third exon of the ovine PRNP gene at codons 136 [7], 141 [8],146 [9], 154 [10], and 171 [11] are closely associated with variation in the phenotypic expression of scrapie. Other regions of PRNP, either independently or in synergy with the coding region, could also influence susceptibility [12]. With extensive and thorough studies, these pathogenic codons are filtered out by artificial selection (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, several studies point out that the expression level of the prion gene could modulate the onset of TSE, particularly in cattle (Sander et al, 2004(Sander et al, -2006Haase et al, 2007). The involvement of the 5' promoter region has been investigated in sheep (Saunders et al, 2009) and cattle (Xue et al, 2008) and it appears that polymorphism in this region could induce different responses to scrapie (Marcos-Carcavilla et al, 2008) and BSE (Brunelle et al, 2008). The analysis of a 23 pb insertion/deletion polymorphism in German and Swiss breed cattle revealed that the deletion is associated to a higher expression level, more frequently A Bird's-Eye View of Veterinary Medicine 524 found in cattle affected with classical BSE.…”
Section: Introductionmentioning
confidence: 99%